Dynamics of recent landslides (<20 My) on Mars: Insights from high-resolution topography on Earth and Mars and numerical modelling. (15th October 2021) - Guimpier, A.; Conway, S.J.; Mangeney, A.; Lucas, A.; Mangold, N.; Peruzzetto, M.; Pajola, M.; Lucchetti, A.; Munaretto, G.; Sæmundsson, T.; Johnsson, A.; Le Deit, L.; et al.
Abstract: Landslides are common features found on steep slopes on Mars and the role of water in their formation is an open question. Our study focuses on three young martian landslides whose mechanism of formation is unknown and knowing their formation mechanism could give us key information on recent martian climate and/or tectonics. They are less than 5 ​km long, and formed during the Late Amazonian Epoch, with an age <20 ​Ma when Mars is thought to have had a hyperarid climate. To better understand the dynamics and formation mechanism of these landslides, we combine two approaches: geomorphic comparison between martian and terrestrial landslides using remote sensing data from the High Resolution Imaging Science Experiment (HiRISE) and the Colour and Stereo Surface Imaging System (CaSSIS), and numerical modelling using a dry granular flow dynamical model. Our geomorphic analysis revealed two contrasting morphologies suggesting differing dynamics and formation mechanisms. Two of the three martian landslides resemble terrestrial rockslides, while the third is more akin to terrestrial mudslides. The numerical modelling, although not fully conclusive, broadly supports our interpretations from the morphological observations. We suggest that the two landslides resembling terrestrial rockslides could have been triggered by shaking by meteorite impact or marsquakes in the absence of water. On the contrary, we suggest liquid water (originating from ground-ice melted by geothermal heat flux) may have been involved in the initiation of the landslide resembling a terrestrial mudslide. Our results show the value of using morphological comparison between martian and terrestrial landslides combined with numerical modelling to inform the hypotheses of landslide-formation on Mars where in situ analysis is not usually possible. Highlights: Three Amazonian martian landslides have similarities with terrestrial analogues. Landslides' morphology suggests two dynamics and formation mechanisms. Liquid water may be implied on recent martian landslide formation as for mudflows on Earth. Young landslide could give key information on recent martian climate and/or tectonics.